The Effect of Halal Label and Product Quality of Purchase Decisions Halal Cosmetic Product Ms Glow - Prihatini, Alvia; Al Farisi, Muhammad Salman; Ferdinand, Novingky (Sharia Business Management Department of STEBIS Bina Mandiri, 2023)
The purpose of this study was to find out determine the effect of halal labeling on purchasing decisions at Ms Glow Jonggol and to determine the effect of Ms Glow product quality on purchasing decisions at Ms Glow Jonggol, then to determine the effect of halal labeling and Ms Glow product quality on purchasing decisions at Ms Glow Jonggol. This type of research is quantitative with a descriptive approach. The population of this study were Ms Glow Jonggol consumers. The sample in this study amounted to 71 respondents. The sampling technique used purposive sampling method. Data collection using questionnaires and data processing techniques used are multiple linear regression processed using SPSS version 22. The results showed that Halal label has a partial effect on purchasing decisions at Ms Glow Jonggol, this can be seen from the value of t count> t table (3.205> 1.667) and sig < 5% (0.002 < 0.05. Product quality has a partial effect on purchasing decisions at Ms Glow Jonggol, this can be seen from the value of t count> t table (5.783> 1.667) and sig < 5% (0.000 < 0.05). Halal labeling and product quality simultaneously affect purchasing decisions at Ms Glow Jonggol, this can be seen from the value of F count 51.050> F table 3.13 and sig < 5% (0.000 < 0.05).